Análise de biomarcadores no cérebro de girinos de rã-touro Aquarana catesbeiana (Shaw, 1802) expostos a materiais particulados atmosféricos - Souza, Iris de Lima (Universidade Federal de São Carlos, 2025)
The productive processes associated with urban expansion and agricultural activities have a high impact on the availability of clean resources for species survival. The excessive use of chemical compounds, derived from metals and metalloids used in these sectors, contributes to the release of particle contaminants into the atmosphere. When deposited in aquatic environments, these particles reach the species that occur in that ecosystem, progressively increasing the toxicity along the food chain. Thus, this study aimed to evaluate the effects of the exposition of brain tissues of tadpoles (Aquarana catesbeiana) to atmospheric particulate material (MPA) using biomarkers of exposure. The results showed that with the significant increase of metals in the water, there was a bioaccumulation of these metals on the brain, surpassing the organ detox capacity, and promoting their systemic distribution. However, the metal's presence did not change the levels of metallothionein (MT) and lipid peroxidation (LPO) but induced the malondialdehyde (MDA) formation. The test of TBARS demonstrated that it is a sensible biomarker for early detection of oxidative stress, overcoming the answer of LPO and MT levels. Thus, it was possible to analyze that tissue exposition to MPA compromises the redox homeostasis and represents an ecotoxicological risk to tadpoles. The findings suggest that atmospheric pollution represents a potential threat to aquatic fauna and to public health, with implications for the food chain and the ecological equilibrium of aquatic environments.
Analysis of biomarkers in the brain of bullfrog tadpoles Aquarana catesbeiana (Shaw, 1802) exposed to atmospheric particulate matter
Keywords: Contaminação; Metais; Estresse Oxidativo; Anfíbios; Contamination; Metals; Oxidative Stress; Amphibians; CIENCIAS BIOLOGICAS::ECOLOGIA; CIENCIAS BIOLOGICAS::BIOQUIMICA